2012
DOI: 10.1371/journal.pone.0030701
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profile of Myeloid-Derived Suppressive Cells from the Bone Marrow of Lysosomal Acid Lipase Knock-Out Mice

Abstract: BackgroundLysosomal acid lipase (LAL) controls development and homeostasis of myeloid lineage cells. Loss of the lysosomal acid lipase (LAL) function leads to expansion of myeloid-derived suppressive cells (MDSCs) that cause myeloproliferative neoplasm.Methodology/Principal FindingsAffymetrix GeneChip microarray analysis identified detailed intrinsic defects in Ly6G+ myeloid lineage cells of LAL knock-out (lal−/−) mice. Ingenuity Pathway Analysis revealed activation of the mammalian target of rapamycin (mTOR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 35 publications
7
51
0
Order By: Relevance
“…36 Second, Affymetrix GeneChip microarray analysis and Ingenuity Pathway Analysis identified the mammalian target of rapamycin (mTOR) as a major signaling pathway in mediating lal À/À MDSCs malfunctions, including immunosuppression and tumor stimulation. 37 Membrane trafficking causes mTOR to shuttle to lysosomes and regulate mTOR signaling. 38,39 The role of PPARg and mTOR pathways in mediating LAL functions needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…36 Second, Affymetrix GeneChip microarray analysis and Ingenuity Pathway Analysis identified the mammalian target of rapamycin (mTOR) as a major signaling pathway in mediating lal À/À MDSCs malfunctions, including immunosuppression and tumor stimulation. 37 Membrane trafficking causes mTOR to shuttle to lysosomes and regulate mTOR signaling. 38,39 The role of PPARg and mTOR pathways in mediating LAL functions needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs were isolated as we previously described (17, 20). Briefly, bone marrow cells were isolated from the femurs and tibias of wild-type ( lal +/+ ) and lal −/− mice.…”
Section: Methodsmentioning
confidence: 99%
“…In ECs, mTOR acts as a regulatory kinase, playing an important role in EC survival, migration, and proliferation (16). We have recently demonstrated that in lal −/− mice, the mTOR pathway was over-activated in bone marrow-derived MDSCs (17). However, it is unknown whether the mTOR pathway is overly activated in lal −/− ECs, and whether over-activation of this pathway is involved in EC dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model, loss of the lysosomal acid lipase function leads to expansion of myeloidderived suppressive cells that cause myeloproliferative Brought to you by | University of Connecticut Authenticated Download Date | 5/31/15 9:15 PM neoplasm. Mice deficient in lysosomal acid lipase displayed a 2.2-fold increase in MK5 transcript levels, suggesting that MK5 may be involved in the myeloid lineage cells toward myeloid-derived suppressive cells (Yan et al , 2012 ). Elevated MK5 levels were observed in prostate cancer, but the biological implication in prostate cancer remains to be determined (Dahlman et al , 2012 ;Whitworth et al , 2012 ).…”
Section: Tumor Suppressionmentioning
confidence: 99%